Reflection on integrating task: a product of the pre-service training of foreign language professional - Fernández González, M. Sc. Deyse Matilde; Camacho Delgado, M. Sc. Paula Esther; Alonso Surí, Lic. Víctor Manuel (Transformación, 2021)
Objective This article aims at describing the findings of the process of assessment and reflection carried out about the integrative task as an alternative to the degree completion exercise by a focus group formed by professors from the English Department, at the University of Las villas. Methods: The authors rely on methods such as analysis of documents, observations, interviews, analysis of students’ outcomes, analysis-synthesis, inductive-deductive and the focus group technique.Results: The framework and structure of the integrative task described as the degree completion exercise is devised. It embraces the integration of contents, communicative, professional and research abilities, components of the curriculum and includes a written report containing the lesson system, its philosophical, pedagogical, psychological, didactic and linguistic fundamentals; the intervention process in the educative practice, and the viva voce.Conclusions: The integrative task may be an alternative to the degree completion exercise. Most of the systems of lessons submitted by the studied sample corroborated that their authors are able to identify their students’ learning level, organize a didactic arrangement of the corresponding content level, select the best methods and techniques, specify the methodological design in the educational practice and assess the students’ learning. The integrative task presented as a system of lessons by the students leads them to a professional and personal development, as they are able to integrate contents; communicative, professional and research abilities; the components of the curriculum, and the education professional functions.
Keywords: teaching assignment; integrated activities; students’ projects; language skills; teaching skills; curriculum